2011
DOI: 10.1029/2011jb008195
|View full text |Cite
|
Sign up to set email alerts
|

Predicted velocity and density structure of the exhuming Papua New Guinea ultrahigh-pressure terrane

Abstract: [1] New electron backscatter diffraction measurements show that the Papua New Guinea (PNG) ultrahigh-pressure (UHP) terrane is dominated by rocks with weakly oriented quartz and feldspar and less abundant strongly oriented hornblende, clinopyroxene, and mica. Velocities measured at high pressures (600 MPa) show that V P is 5.8-6.3 km/s for gneiss samples, 6.5-7.7 km/s for amphibolite, and 7.7-8.2 km/s for eclogite and V S is 3.4-3.9 km/s for gneiss, 4.0-4.4 km/s for amphibolite, and 4.5-4.6 km/s for eclogite. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
43
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 38 publications
(47 citation statements)
references
References 44 publications
3
43
1
Order By: Relevance
“…The average bulk anisotropy values for chlorite schists, mica schists, phyllites, sillimanite‐mica schists, and amphibole schists at 600 MPa are 12.0 ± 4.1%, 12.8 ± 5.9%, 12.8 ± 9.0%, 17.0 ± 4.9%, and 12.9 ± 3.2% respectively, indicating that such schists are much more anisotropic in V p (13.2 ± 6.0%) than other categories of metamorphic rocks such as granitic gneisses, felsic mylonites, granulites, and peridotites [e.g., Ji et al , , ; Mainprice and Silver , ; Saruwatari et al , ], in which the constituent minerals have geometrically complex seismic responses that interfere destructively to produce either low anisotropy or nearly isotropic properties. The characteristically high seismic anisotropy of the schists is attributed to strongly aligned phyllosilicates such as mica (Figure ) [also see Brownlee et al , ; Erdman et al , ; Ji et al , ; Kern and Wenk , ; Mahan , ; Meltzer and Christensen , ; Shapiro et al , ] as shown also by microstructural observations (e.g., Figure ). However, the average V p anisotropy values in the foliation plane or foliation anisotropy are much smaller than the bulk anisotropy values at the same pressure: 2.4 ± 1.9% for phyllites, 3.3 ± 2.7% for mica schists, 4.1 ± 2.6% for chlorite schists, 6.8 ± 3.4% for sillimanite‐bearing mica schists, and 5.2 ± 1.9% for amphibole schists.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…The average bulk anisotropy values for chlorite schists, mica schists, phyllites, sillimanite‐mica schists, and amphibole schists at 600 MPa are 12.0 ± 4.1%, 12.8 ± 5.9%, 12.8 ± 9.0%, 17.0 ± 4.9%, and 12.9 ± 3.2% respectively, indicating that such schists are much more anisotropic in V p (13.2 ± 6.0%) than other categories of metamorphic rocks such as granitic gneisses, felsic mylonites, granulites, and peridotites [e.g., Ji et al , , ; Mainprice and Silver , ; Saruwatari et al , ], in which the constituent minerals have geometrically complex seismic responses that interfere destructively to produce either low anisotropy or nearly isotropic properties. The characteristically high seismic anisotropy of the schists is attributed to strongly aligned phyllosilicates such as mica (Figure ) [also see Brownlee et al , ; Erdman et al , ; Ji et al , ; Kern and Wenk , ; Mahan , ; Meltzer and Christensen , ; Shapiro et al , ] as shown also by microstructural observations (e.g., Figure ). However, the average V p anisotropy values in the foliation plane or foliation anisotropy are much smaller than the bulk anisotropy values at the same pressure: 2.4 ± 1.9% for phyllites, 3.3 ± 2.7% for mica schists, 4.1 ± 2.6% for chlorite schists, 6.8 ± 3.4% for sillimanite‐bearing mica schists, and 5.2 ± 1.9% for amphibole schists.…”
Section: Discussionmentioning
confidence: 89%
“…The dominant b ‐slip fabric was reported for muscovite in a quartzite (sample CB‐q consisting of 95% quartzite, 3% muscovite, and 2% kyanite [ Ward et al , ]). The a + b slip‐induced fabric pattern was reported for biotite in quartzofeldspathic gneisses from the exhuming Papua New Guinea ultrahigh‐pressure terrane [ Brownlee et al , ] and for a quartz‐bearing amphibolite (sample GR‐a), and muscovite in a quartzite (sample ISR‐q consisting of 95% quartz, 3% muscovite, and 2% sillimanite) [ Ward et al , ].…”
Section: Electron Backscatter Diffraction‐measured Cpo and Calculatedmentioning
confidence: 99%
See 2 more Smart Citations
“…At 550 °C and 0.8 GPa, they show that Vs lies near 3.8 km/s, and never below 3.7 km/s. While temperature variations are poorly known for these compositions, owing to the competing effects of thermal expansion and dehydration‐mediated reactions, most direct calculations on dry felsic rocks are unable to produce Vs < 3.6 km/s (e.g., Abers et al, ; Brownlee et al, ). Across the United States, at 25‐km depth Vs is less than 3.6 km/s in only 3.4% of the area resolved by Shen and Ritzwoller (), largely beneath volcanic areas of the Cascades or Basin and Range.…”
Section: Discussionmentioning
confidence: 99%